Efeito inibitório dos óleos essenciais de Origanum vulgare L. e Rosmarinus officinalis L. sobre bactérias patogênicas contaminantes de hortaliças minimamente processadas - Barbosa, Isabella de Medeiros (2015)
Minimally processed vegetables are ready-to-eat products that undergo to a physical modification processes such as cutting, peeling and slicing, but preserve characteristics of a fresh food. When processed under unsatisfactory sanitary conditions, these products may represent microbiological risk and, therefore, sanitation becomes a critical step processing. In the present study the effects of the application of the essential oils (EOs) from Origanum vulgare L. – oregano (OVEO) and Rosmarinus officinalis L. – rosemary (ROEO), alone or combined at sub-inhibitory concentrations were assessed against the pathogenic bacteria contaminants of minimally processed vegetables, Listeria monocytogenes, Escherichia coli and Salmonella Enteritidis. The identification of the EOs’ constituents was performed by gas chromatography–mass spectrometry (GC-MS). The inhibitory effects were evaluated by determination of minimum inhibitory concentration (MIC), fractional inhibitory concentration index (FICI) and assessment of viable cell counts in vegetable broth and artificially infected vegetable over time. Thymol and eucalyptol were the major compounds identified in OVEO and ROEO, respectively. MIC value of OVEO was 0.6 μL/mL against the test strains either in single and mixed inoculum. MIC value of ROEO was 5 μL/mL against L. monocytogenes and E. coli and 10 μL/mL against S. Enteritidis in single inocula, while it was 10 μL/mL against the mixed inoculum. FICI of the combined EOs was 0.5 against the mixed bacterial inoculum, suggesting synergic interaction. The incorporation of OVEO and ROEO alone (MIC) or at different sub-inhibitory concentrations in vegetable broth resulted in decrease of viable cell counts of all test strains along the 24 h. A ≥ 3 log cycles reduction in viable cell count of L. monocytogenes, E. coli and S. Enteritidis was observed after exposure to OVEO at MIC. When exposed to ROEO at MIC, the same reduction was observed for cells of L. monocytogenes and E. coli, while S. Enteritidis presented smaller decrease (up to 1.7 log cycles) in viable cell counts. The incorporation of OVEO and ROEO combined at sub-inhibitory concentrations resulted in a decrease in initial viable counts of all strains tested, although the time requested to stablish this decrease varied according to the strain and amount of each EO in combination. Likewise, the EOs applied alone or in combination reduced the viable cell counts of all test strains when essayed in artificially infected vegetables. However, the exposure of vegetables to EOs for 10 minutes caused a greater reduction in viable cell counts compared to results obtained after 5 minutes of exposure. In both essays was observed that the inhibitory effects of the EOs varied according to the time and strain. These findings reinforce the rational use of OVEO and ROEO combined at sub-inhibitory concentrations to guarantee the safety and extend the shelf-life of fresh vegetables. It is also suggested carrying out scientific researches aimed to study the toxicity in animals and /or human cells, in order to ensure the health safety of these oils when used in food.